Relative and Absolute Tense Interpretation in Modern Hebrew - Hatav, Galia (Hebrew studies, 2010)
It is well acknowledged that Modern Israeli Hebrew has three distinctive morphological tenses—past, future, and present. The three forms may be used not only as absolute tenses, locating the event in time with respect to the speech-time, but also as relative tenses, locating situations with respect to other times in the past or the future. The main concern of this paper is to determine the semantic and syntactic conditions for the absolute and relative interpretation of the Hebrew tenses. , Applying recent semantic analyses to Hebrew, the paper first shows that a relative tense interpretation is only possible in intentional contexts; in particular, when possible worlds other than the actual one are involved. The paper then proceeds to show that tenses in the scope of intentional context must have a relative reading in the case of complement clauses, but in the case of relative and matrix clauses, a relative tense reading is only optional, where the tense may be ambiguous between absolute and relative readings. Finally, the paper discusses discourse structure and pragmatic factors that may contribute to tense interpretation.